The Impact of Age at Time of Ileal Pouch Anal Anastomosis on Short and Long-Term Outcomes in Adults. Issue 8 (26th April 2018) - McKenna, Nicholas P; Mathis, Kellie L; Pemberton, John H; Lightner, Amy L
Abstract: Background: There is limited knowledge on ileal pouch anal anastomosis (IPAA) function when performed on patients older than age 50 years. The aim of this study was to determine if surgery on those older than age 50 years impacts short-term complications or long-term function. Methods: A retrospective review of all patients undergoing IPAA for chronic ulcerative colitis at a single tertiary referral center between 2002 and 2013 was conducted. Short-term postoperative complications and long-term function and quality of life were analyzed according to age at pouch formation (age >50 vs age ≤50 years). Results: A total of 911 patients who underwent IPAA (542 male) were included, with 178 patients (20%) age >50 years and 733 (80%) ≤50 years. Patients >50 years had higher American Society of Anesthesiology score (ASA) scores and increased rates of obesity and dysplasia or cancer at the time of colectomy, and were less often on steroids (all P < 0.01). Over a median follow-up of 5 years, older patients reported increased daytime incontinence (60% vs 37%, P < 0.01) and pad usage (34% vs 11%, P < 0.01) at up to 1.5 years post-IPAA, after which time the groups became similar. Other functional outcomes, including pouch failure and quality of life, were similar between the 2 groups across the follow-up periods. Conclusion: Performing an IPAA on carefully selected patients older than age 50 years has minor, transient differences in pouch function compared with patients younger than age 50 years. Assuming appropriate patient selection, IPAA should continue to be offered to older patients without increased risk of compromised function or of pouch failure.